Crisponi syndrome is caused by mutations in the CRLF1 gene and is allelic to cold-induced sweating syndrome type 1 - Crisponi, Laura; Crisponi, Giangiorgio; Meloni, Alessandra; Toliat, Mohammad Reza; Nurnberg, Gudrun; Usala, Gianluca; Uda, Manuela; Masala, Marco; Hohne, Wolfgang; Becker, Christian; Marongiu, Mara; Chiappe, Francesca; et al. (American journal of human genetics, 2007)
Crisponi syndrome is a severe autosomal recessive condition that is phenotypically characterized by abnormal, paroxysmal muscular contractions resembling neonatal tetanus, large face, broad nose, anteverted nares, camptodactyly, hyperthermia, and sudden death in most cases. We performed homozygosity mapping in five Sardinian and three Turkish families with Crisponi syndrome, using high-density single-nucleotide polymorphism arrays, and identified a critical region on chromosome 19p12-13.1. The most prominent candidate gene was CRLF1, recently found to be involved in the pathogenesis of cold-induced sweating syndrome type 1 (CISS1). CISS1 belongs to a group of conditions with overlapping phenotypes, also including cold-induced sweating syndrome type 2 and Stuve-Wiedemann syndrome. All these syndromes are caused by mutations of genes of the ciliary neurotrophic factor (CNTF)-receptor pathway. Here, we describe the identification of four different CRLF1 mutations in eight different Crisponi-affected families, including a missense mutation, a single-nucleotide insertion, and a nonsense and an insertion/deletion (indel) mutation, all segregating with the disease trait in the families. Comparison of the mutation spectra of Crisponi syndrome and CISS1 suggests that neither the type nor the location of the CRLF1 mutations points to a phenotype/genotype correlation that would account for the most severe phenotype in Crisponi syndrome. Other, still-unknown molecular factors may be responsible for the variable phenotypic expression of the CRLF1 mutations. We suggest that the syndromes can comprise a family of "CNTF-receptor-related disorders," of which Crisponi syndrome would be the newest member and allelic to CISS1.